PARENTING: POLA ASUH ANAK DENGAN METODE TETEP-ANTEP-MANTEP - Putro, Die Bhakti Wardoyo; Widowati, Widowati; Azizah, Shefia Nur (ABDI MAKARTI, 2024)
This community service aims to apply the teachings of Tamansiswa, namely the Three Education Centers, through parenting patterns for children. This parenting style is instilling confidence in oneself which is known as Tetep-Mantep-Antep. Parents who are members of the as-Salam group in Genjahan sub-district, Ponjong, Gunungkidul have not been familiar with various Tamansiswa teachings which can influence the development of their child's personality in the future. In fact, these teachings are closely related to the local wisdom of the local community. This community service is carried out using lecture, discussion, question and answer methods, as well as discussions between participants with their respective experiences. Discussions between participants were carried out because some of the participants had actually practiced Tamansiswa's teachings indirectly. The results of this service show positive things. The enthusiastic participants took an active role in the activities. They were inspired by their enthusiasm to realize Tamansiswa's teachings, especially the Fixed-Steady-Antep parenting pattern in parenting patterns based on their respective environments according to their culture and beliefs